KAJIAN MAKNA PADA LAGU KURIK KUNDI KARYA SUHAIMI ZAIN - Masniati, Lidia; Fauzi, Mohd.; Jefrizal, Jefrizal; Kafrawi, Muhammad; Evizariza, Evizariza (Universitas Lancang Kuning, 2024)
This research aims to describe the meaning of the song Kurik Kundi by Suhaimi Zein. The analysis focuses on the connotative meaning and social values in the song. This research uses a qualitative approach. The data discussed are words, phrases, and clauses sourced from the Kurik Kundi song. The method used to collect data is observation and the data analysis method is the inductive method. The results of the research show the connotation meaning found in the songs. There are words and phrases indicating the relationship between words and phrases with social life and Malay culture. The social values ​​contained in the song of Kurik Kundi indicate the polite attitude of Malays towards fellow Malays and other people. Good manners in expressing the daily attitudes of Malay people. The enthusiasm in carrying out activities, and cooperation carried out by Malay people to achieve common goals in society.